ANALISIS PENGARUH VARIASI SUDUT SAMBUNGAN BELOKAN PIPA TERHADAP PRESSURE DROP ALIRAN PIPA - Tia Setiawan; Slamet Riyadi; Bayu Bayu Faisal Nugraha (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
In the water distribution process, whether in industry or housing, there are usually pipe bends. Every pressure pipe that flows the fluid must experience a head loss or energy loss. The amount of this loss is influenced by several factors, including: diameter, inlet and outflow, viscosity, and the angle of the arch pipe connection. This study aims to determine the effect of variations in connection points at pipe bends on energy losses and pressure drops. To do this, the research uses experiments with several types of turns according to the conditions that occur in the field. The results showed that the pressure drop was influenced by the water discharge and the head loss of the pipe flow. At the 45obend connection, the largest pressure drop is at node 10, which is 0.7052 bar. While at the 30o turn connection, the biggest pressure loss is at node 11 with a value of 8.5948 bar. And the last turning connection, with a turning angle of 60o, loses pressure of 0.0042 bar